Effects of laser photherapy on bone defects grafted with mineral trioxide aggregate, bone morphogenetic proteins, and guided bone regeneration: A Raman spectroscopic study - Pinheiro, Antonio L. B.; Aciole, Gilberth T. S.; Cangussú, Maria Cristina T.; Pacheco, Marcos T. T.; Silveira Jr, Landulfo (Journal of biomedical materials research. Part A, 2010)
We have used Raman analysis to assess bone healing on different models. Benefits on the isolated or combined use of mineral trioxide aggregate, bone morphogenetic proteins, guided bone regeneration and laser on bone repair have been reported, but not their combination. We studied peaks of hydroxyapatite and CH groups on defects grafted with MTA, treated or not with laser, BMPs, and GBR. Ninety rats were divided in 10 groups each, subdivided into three subgroups. Laser (λ850 nm) was applied at every other day for 2 weeks. Raman readings were taken at the surface of the defect. Statistical analysis (CHA) showed significant differences between all groups (p = 0.001) and between Group II and all other (p < 0.001), but not with Group X (p = 0.09). At day 21 differences were seen between all groups (p = 0.031) and between Groups VIII and X when compared with Groups VI (p = 0.03), V (p < 0.001), IV (p < 0.001), and IX (p = 0.04). At the end of the experimental period no significant differences were seen. On regards CH, significant differences were seen at the 15th day (p = 0.002) and between Group II and all other groups (p < 0.0001) but not with control. Advanced maturation on irradiated bone is because of increased secretion of calcium hydroxyapatite (CHA) that is indicative of greater calcification and resistance of the bone. We conclude that the association of the MTA with laser phototherapy (LPT) and/or not with GBR resulted in a better bone repair. The use of the MTA associated to IR LPT resulted in a more advanced and quality bone repair. © 2010 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2010.